A Game Optimization Scheduling Strategy of Active Distribution Network With Multi-Microgrid Sharing Energy Storage - Li, Fei; Li, Xianshan; Fang, Zijian; Zhang, Lei (Frontiers in Energy Research, 2022)
In multi-microgrid grid-connected system, a MGCO is formed to participate in the optimization scheduling of ADN by sharing ES, which can promote the efficient utilization of resources and obtain win-win interests for all participants. According to the complementary characteristics of the ES behaviors and energy production-consumption of MGs, a game scheduling model of ADN with MGCO for sharing ES is established to obtain energy reciprocity and balance the interest of both parties. ADN formulates the ToU price policy to maximize the operational benefits, and MGCO responds the price to obtain each member's energy dispatching strategy for minimizing the total operating costs. Furthermore, all members in the MGCO distribute the cooperation surplus based on Shapely value method. The example results show that the proposed game model can balance the benefits between the ADN and multi-microgrid with sharing ES, and maximize the mutual benefits of MGCO through energy reciprocity.